Contribution of Women in Scientific Publications – A Comparative Study Before and After COVID-19 (Indian Journal of Extension Education, 2023)
Emerging evidence shows that women authors are not well represented in publications resulting in gender gaps in publications. 548 original research papers published between 2019 to 2021 in three journals selected randomly from the list of quarterly published journals from India under the Science Citation Index Expanded (SCIE) core collection. According to the gender-wise contributions in scientific publications, there was a significant disparity between authors (male and female). Among national-level publications, the percentage of female authors in science journals published in 2019 and 2020, before the COVID-19 pandemic was 20.25 per cent, while their contribution to science journals published during COVID-19 reduced to 17.80 per cent. The contribution of women authors in science journals was decreased by 2.47 per cent during the COVID-19 pandemic. There was a significant divergence between the average number of authors and the average number of female authors in each issue.